Influenza A virus continues to circulate among children in Linyi, northern China, after the relaxation of COVID-19 control measures - Tiegang Lv; Jie Chen; Huafeng Li; Xiaoyan Chen; Na Zhang; Chunling Ma; Yanli Zhang; Pengfei You (Scientific Reports)
Abstract Following the relaxation of control measures for COVID-19 in China in December 2022, there was a resurgence of influenza A among children in Linyi. This research aims to analyze the epidemiology and genetic characteristics of influenza A viruses circulating among children in Linyi from April 2022 to March 2024. Throat swab specimens were collected from children with influenza-like illness (ILI), and the types of influenza were identified. The hemagglutinin (HA) genes of influenza A viruses were amplified using reverse transcription-polymerase chain reaction (RT-PCR) and then sequenced. Subsequently, the gene characteristics and phylogenetics of these sequences were analyzed. A total of 6258 cases of influenza A were tested from 54,926 children with ILI over two years, showing three epidemic waves: one in summer 2022 and two in spring and winter 2023. The epidemic waves in summer 2022 and winter 2023 were caused by influenza A(H3N2) viruses. In spring 2023, influenza A(H1N1)pdm09 viruses accounted for 77.1% and A(H3N2) viruses accounted for 22.9%, respectively. The influenza A(H1N1)pdm09 viruses belonged to clade 6B.1A.5a.2a, while the influenza A(H3N2) viruses evolved from clade 3C.2a1b.2a.1a to 3C.2a1b.2a.2a.3a.1. Compared with the vaccine strain of the Northern Hemisphere of the current year, multiple amino acid substitutions and glycosylation sites changes were observed in the HA protein that most likely resulted in antigenic drift. The influenza A viruses have been circulating and evolving persistently in Linyi from 2022 to 2024. Continuous surveillance is essential for comprehending the dynamics of influenza in the post-COVID-19 era.